Markers for gastrointestinal autoimmune disorders in patients with type 1 diabetes mellitus - Olga Sergeevna Derevyanko; Nadezhda Sergeevna Dalantaeva; Elena Vladimirovna Pekareva; Olga Nikolaevna Ivanova; Nikolay Petrovich Goncharov; Tatiana Vasil'evna Nikonova; Olga Mikhailovna Smirnova (Сахарный диабет)
Aim.  to assess the occurrence of autoantibodies characteristic of autoimmune pancreatitis and gastritis in patients with type 1 diabetes mellitus (T1DM), and to analyze clinical features of positive subjects. Materials and Methods.  84 patients (39 male, 45 female) with T1DM were subdivided into two groups and underwent biochemical, immunologic and instrumental examination. Results.  Markers for gastrointestinal autoimmune disorders were found to be highly prevalent in patients with T1DM, even in those asymptomatic according to instrumental diagnostic methods. Conclusion. Our data suggests that T1DM patients are at higher risk of corresponding, possibly asymptomatic autoimmune disorders.